The Mental Health Level Among a Sample of Married Syrian Underage Females - Al-Shawashereh, Omar; Jeet, Tariq (Jordan Journal of Educational Sciences, 2017)
The study aimed to examine the mental health level among a sample of married Syrian underage refugee females in Jordan. The sample of the study consisted of (301) Syrian underage refugee females who have been married in Jordan. To achieve the aim of the study, a mental health scale was developed. The results of the study indicated that the mental health level of Syrian underage refugee females who have been married in Jordan was moderate. Results also revealed statistically significant differences in mental health among Syrian underage refugee females who have been married in Jordan due to the variables of (parents' work status, age at marriage, and the reasons for early marriage) ,in favor of females with working parents in comparison with un-working parents. Also, the results were in favor of underage refugee females who married at the age of 17 in comparison with age 13 or 14, and in favor of Syrian underage females refugees who have been married in Jordan for the reason of having children in comparison with those who (do not feel safe, the absent of their parents, being poor or they got married based on their parents’ choice or recommendations).